On the taxonomic position of Hesperophanes cinereus Blanchard in Gay, 1851 (Coleoptera: Cerambycidae) - Vitali, Francesco (Zootaxa, 2019)
Hesperophanes cinereus was described by Blanchard (1851) in the Fauna of Coleoptera of Chile and mentioned as such by Fairmaire & Germain (1859) and Aurivillius (1912). Noting that this name was a junior secondary homonym of the well-known European species H. cinereus (Villers, 1789), originally described as Cerambyx cinereus, Plavilstshikov (1917) proposed H. gayi as a substitute name for Blanchard’s species.